Propofol pharmacokinetics and pharmacodynamics—a perspective in minimally invasive extracorporeal circulation. (9th May 2021) - Condello, Ignazio; Santarpino, Giuseppe; Fiore, Flavio; Di Bari, Nicola; Speziale, Giuseppe; Moscarelli, Marco; Nasso, Giuseppe
Abstract: There is limited evidence as to the pharmacokinetic changes expected in adults with extracorporeal technologies. Drugs may be taken up by various components of the cardiopulmonary bypass circuit itself. Issues include the increased volume of the circuit leading to haemodilution; the sequestration of lipophilic drugs within the circuit tubing; and the absorption of proteins, especially albumin, onto the circuit, which can result in increased free drug. However, in this context, the aspect of pharmacokinetics and pharmacodynamics during minimally invasive extracorporeal circulation has not been described and evidenced by scientific studies. In this single-centre control study of 60 patients undergoing isolated coronary artery bypass grafting, we present the results focused on postoperative albumin values and intraoperative propofol dosages in patients undergoing surgery with minimally invasive ( n  = 30) versus conventional extracorporeal circulation ( n  = 30). In the minimally invasive extracorporeal circulation group, a lower propofol dosage titrated to a bispectral index of 40–45 was used during coronary artery bypass grafting, and an improvement of postoperative concentration of serum albumin was observed compared to the conventional extracorporeal circulation group. Abstract : There is limited evidence as to the pharmacokinetic changes expected in adults with extracorporeal technologies.